Regulation of Vacuolar pH and Its Modulation by Some Microbial Species - Huynh, Kassidy K. (American Society for Microbiology (ASM), 2007)
Summary: To survive within the host, pathogens such as Mycobacterium tuberculosis and Helicobacter pylori need to evade the immune response and find a protected niche where they are not exposed to microbicidal effectors. The pH of the microenvironment surrounding the pathogen plays a critical role in dictating the organism's fate. Specifically, the acidic pH of the endocytic organelles and phagosomes not only can affect bacterial growth directly but also promotes a variety of host microbicidal responses. The development of mechanisms to avoid or resist the acidic environment generated by host cells is therefore crucial to the survival of many pathogens. Here we review the processes that underlie the generation of organellar acidification and discuss strategies employed by pathogens to circumvent it, using M. tuberculosis and H. pylori as examples.